Offender interviews: implications for intelligence-led policing. Issue 1 (13th December 2018) - Summers, Lucia; Rossmo, D. Kim
Abstract : Purpose: Intelligence-led policing (ILP) involves the analysis of data to inform the development and implementation of strategic actions aimed at more efficiently reducing crime. The purpose of this paper is to examine how chronic acquisitive offenders – a focus of ILP – respond to police patrol, and how this knowledge can be turned into actionable strategies to reduce crime. Design/methodology/approach: Interviews were conducted with 137 chronic offenders who had multiple convictions for burglary, robbery and/or vehicle crime. The interviews involved the collection of both qualitative and quantitative data, including responses to situational crime vignettes. Findings: When encountering police patrols, criminals were initially more likely to displace (e.g. committing crime elsewhere and/or later in the day) than to desist from offending. Some of the conditions under which police patrol was most effective were identified, including offenders' fear of being recognized by officers. Repeated thwarted crime attempts appeared to be most impactful, with even the most chronic offenders becoming "worn down." Practical implications: The profiles of top offenders should be systematically disseminated to front line officers to augment the effectiveness of police patrol and minimize the possibility of crime displacement. Originality/value: Offender interviews are a valuable source of information but they have been underutilized within an ILP framework. This research illustrates how offender interview research can inform and support the role of police in preventing crime.